Perception of Micro, Small and Medium Enterprises (MSMEs) in Pekanbaru towards the Rupiah Redenomination Policy Plan - Rizaldi, Rizky; Zamaya, Yelly (Sosio e-Kons, 2025)
This study aims to analyze the perceptions of Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City regarding the planned Rupiah redenomination policy. Redenomination, which involves simplifying the nominal value of the currency by removing several zeros, is expected to enhance the efficiency of the payment system and promote economic growth. However, this policy has also raised concerns among MSME actors regarding adjustment costs, potential price increases, and a decline in public purchasing power. The research method employed a mixed-method approach, with a sample of 100 MSME respondents selected through stratified random sampling. Data were collected through questionnaires and interviews, then analyzed using the Chi-Square test and cross-tabulation. The results indicate differing perceptions among MSME actors regarding the purpose, benefits, and impacts of redenomination. Some MSME actors view the policy positively, believing it can simplify transaction calculations, increase efficiency, and attract foreign investment. However, others are concerned about adjustment costs, potential price hikes, and public misunderstandings of the policy. This study concludes that intensive socialization and education from Bank Indonesia are necessary to improve public understanding, especially among MSME actors, regarding the benefits and challenges of redenomination. Recommendations for further research include expanding the scope and conducting more in-depth analysis to obtain a more comprehensive picture of MSME actors' perceptions of the redenomination policy.